Assessing the efficacy and mechanisms of glycol-contaminated water treatment through floating treatment wetlands - Lyu, Tao; Williams, Randy; Exton, Benjamin; Grabowski, Robert C. (IWA Publishing, 2023)
The growing concerns surrounding water pollution and the degradation of ecosystems worldwide have led to an increased use of nature-based solutions (NbSs). This study assessed the feasibility of using floating treatment wetlands (FTWs) as an NbS to treat propylene glycol-contaminated water and quantitatively investigated different removal pathways. With an environmentally relevant concentration of propylene glycol (1,250 mg/L), FTWs containing Acorus calamus and mixed species demonstrated the highest average glycol mass removal efficacy (99%), followed by Carex acutiformis (98%), Juncus effusus (93%), and the control group without plants (10%) after 1 week. Additional mesocosm-scale experiments with varying FTW configurations, including surface coverage to reduce evaporation and photodegradation processes, and the addition of antibiotics to inhibit microbial activity, were conducted to quantify glycol removal pathways. Mass balance analysis results revealed that microbial biodegradation (33.3–39.7%) and plant uptake (37.9–45.2%) were the primary pathways for glycol removal. Only 15.5–19.5% of the glycol removal via evaporation and photodegradation was accounted in this study, which may be attributed to the mesocosm experimental setup (static water and no wind). Aligned with the broader discussion regarding biodiversity improvements and carbon storage capacity, this study demonstrated that FTWs are an environmentally friendly and effective NbS for addressing glycol-contaminated water.
Keywords: biodiversity; constructed wetlands; green technology; multi-benefits; propylene glycol; volatile organic compound (VOCs)